The dictionary of imaginary places : the newly updated and expanded classic - Manguel, Alberto (San Diego : Harcourt, 1999)
Describes and visualizes over 1,200 magical lands found in literature and film, discussing such exotic realms as Atlantis, Tolkien's Middle Earth, and Oz.
Onderzoek KASK (1KA-OF1001)
boek